Formation of Child Morality through Muwang Sangkal Dance Movement in Elementary School - Tri Sukitman (Jurusan Sastra Indonesia, 2019)
The development of a country will not be separated from the role of modernization and globalization. The country is said to be advanced if a country is based on modernity. So when modernization and globalization is a necessity, the Indonesian state must also be able to adjust to these developments. So that the current of modernization and globalization will have a positive and negative impact on the nation and the State. One of the impacts is the decline of national morality. The next generation of the nation has begun to forget the values of local wisdom and be more proud of foreign cultures. This is why, it needs serious handling, especially in the world of education. Morality needs to be established and strengthened, so the role of schools is very much needed in order to improve the decline of moral values caused by a lack of interest in local culture. One way to overcome these problems is by teaching children about Muwang Sangkal dance. Because in every movement in Muwang Sangkal dance has philosophical values related to moral values. So that by teaching children the concepts and practices of Muwang Sangkal dance will restore the values of national morality that have begun to be eroded by the flow of globalization.